2021
DOI: 10.3390/molecules26154480
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics of the Edible Brown Alga Wakame (Undaria pinnatifida) by Liquid Chromatography Coupled to Electrospray Ionization and Tandem Mass Spectrometry

Abstract: The lipidome of a brown seaweed commonly known as wakame (Undaria pinnatifida), which is grown and consumed around the world, including Western countries, as a healthy nutraceutical food or supplement, was here extensively examined. The study was focused on the characterization of phospholipids (PL) and glycolipids (GL) by liquid chromatography (LC), either hydrophilic interaction LC (HILIC) or reversed-phase LC (RPLC), coupled to electrospray ionization (ESI) and mass spectrometry (MS), operated both in high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 61 publications
3
23
0
Order By: Relevance
“…Lipid composition in seaweeds has been investigated in the last decade by lipidomics with the purpose to reveal the healthy benefits and added value attributed to seaweeds. A widely used method in lipidomic studies is ultra-high-performance liquid chromatography coupled with high-resolution tandem mass spectrometry (UPLC–HRMS) . With the advantage of analyzing both polar and nonpolar metabolites as well as lipids, UPLC–HRMS has been widely used to reveal the polar lipid profiles of several brown seaweed species. ,,, These previous studies have highlighted the wide variety of polar lipid molecules in brown seaweeds, constituted mainly by phospholipids (PLs), glycolipids (GLs), and betaine lipids (BLs), which are the main constituents of cell membranes, thylakoid membranes, and signaling molecules, respectively . Among them, GLs composed of glycoglycerolipids and glycosphingolipids are predominant, accounting for approximately 50% of the total lipid content .…”
Section: Introductionmentioning
confidence: 99%
“…Lipid composition in seaweeds has been investigated in the last decade by lipidomics with the purpose to reveal the healthy benefits and added value attributed to seaweeds. A widely used method in lipidomic studies is ultra-high-performance liquid chromatography coupled with high-resolution tandem mass spectrometry (UPLC–HRMS) . With the advantage of analyzing both polar and nonpolar metabolites as well as lipids, UPLC–HRMS has been widely used to reveal the polar lipid profiles of several brown seaweed species. ,,, These previous studies have highlighted the wide variety of polar lipid molecules in brown seaweeds, constituted mainly by phospholipids (PLs), glycolipids (GLs), and betaine lipids (BLs), which are the main constituents of cell membranes, thylakoid membranes, and signaling molecules, respectively . Among them, GLs composed of glycoglycerolipids and glycosphingolipids are predominant, accounting for approximately 50% of the total lipid content .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of RP columns, C18 is the most widely used but others can also be used, such as C8 and C30. [30][31][32] Different instruments have been used to address the challenges of marine lipidomics. Low resolution instruments such as Triple Quadrupole and Q-Traps have been mainly used for targeted analysis and Linear Ion Trap for untargeted analysis.…”
Section: Mass-spectrometry Based Lipidomic Methodologymentioning
confidence: 99%
“…In the case of RP columns, C18 is the most widely used but others can also be used, such as C8 and C30. 30–32…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They mainly focus on the FA composition and aim to establish a relationship between the FA profile and PUFA abundance with antioxidant activity [70]. Algae extracts are complex mixtures that comprise different classes of lipids, including neutral lipids, such as triacylglycerol (TAG), sterols, free FA; and polar lipids, such as phospholipids, glycolipids, and betaine lipids [73][74][75][76][77]. Recently, it has been suggested that polar lipids such as phospholipids, are better at delivering omega-3 PUFA [78].…”
Section: Algae Lipids With Antioxidant Activitymentioning
confidence: 99%